Contribution of MS-Based Proteomics to the Understanding of Herpes Simplex Virus Type 1 Interaction with Host Cells - Santamaría, Enrique; Sánchez-Quiles, Virginia; Fernández-Irigoyen, Joaquín; Corrales, Fernando J. (Frontiers in Microbiology, 2012)
Like other DNA viruses, herpes simplex virus type 1 (HSV-1) replicates and proliferates in host cells continuously modulating the host molecular environment. Following a sophisticated temporal expression pattern, HSV-1 encodes at least 89 multifunctional proteins that interplay with and modify the host cell proteome. During the last decade, advances in mass spectrometry applications coupled to the development of proteomic separation methods have allowed to partially monitor the impact of HSV-1 infection in human cells. In this review, we discuss the current use of different proteome fractionation strategies to define HSV-1 targets in two major application areas: (i) viral-protein interactomics to decipher viral-protein interactions in host cells and (ii) differential quantitative proteomics to analyze the virally induced changes in the cellular proteome. Moreover, we will also discuss the potential application of high-throughput proteomic approaches to study global proteome dynamics and also post-translational modifications in HSV-1-infected cells that will greatly improve our molecular knowledge of HSV-1 infection.